Salvia libanotica improves glycemia and serum lipid profile in rats fed a high fat diet. Issue 1 (December 2015) - Bassil, Maya; Daher, Costantine; Mroueh, Mohammad; Zeeni, Nadine
Abstract Background Salvia libanotica (S. Libanotica ) is a commonly used herb in folk medicine in Lebanon and the Middle East. The present study aimed to assess the scientific basis for the therapeutic use ofS. libanotica in glycemia and to evaluate its effects on lipemia and abdominal fat. Methods Animals were fed a high-fat diet and allocated into a control and three experimental groups (GI, GII and GIII) receiving incremental doses of the plant water extract in drinking water (50, 150 and 450 mg/Kg body weight respectively) for six weeks. Results The intake ofS. libanotica extract was associated with a significant decrease in fasting serum glucose (102.9 ± 10.8 in GII and 87.5 ± 6.4 in GIII vs. 152.1 ± 7.9 mg/dl in controls) and a two fold increase in fasting serum insulin (GIII) and liver glycogen content (GII and GIII). Group III also had better glucose tolerance following intraperitoneal glucose challenges. Additionally, the plant extract intake produced a significant improvement in serum HDL (34.4 ± 2.4 in GIII vs. 27.2 ± 1.9 mg/dl in controls) and HDL/LDL cholesterol ratio (2.79 ± 0.32 in GII and 3.02 ± 0.31 in GIII vs. 1.74 ± 0.18 in controls), as well as a decrease in abdominal fat. Conclusion The current study is the first to demonstrate that the chronic intake ofS. libanotica infusion helps in the prevention of high fat-induced hyperglycemia and dyslipidemia. This supports the plant use as a remedy for the prevention of type 2 diabetes and cardiovascular diseases.